1995
DOI: 10.1111/j.1476-5381.1995.tb15051.x
|View full text |Cite
|
Sign up to set email alerts
|

Central cardiovascular effects of acetylcholine in the conscious dog

Abstract: release but these responses were shorter (less than 10 min) in the conscious dogs than in anaesthetized dogs (more than 10 min). Moreover, we detected in the response to the central cholinergic stimulation in the conscious dogs a significant increase in plasma adrenaline levels and biphasic changes in heart rate which were not described previously in the anaesthetized dog.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Vasopressin and electrolytes. Urine from NSE-AT1A transgenic (n ϭ 30) and control littermates (n ϭ 36) was analyzed for vasopressin levels using radioimmunoassay, as described (7). In addition, urines were diluted (1:4), and osmolality was determined using a vapor pressure osmometer (Wescor Instruments).…”
Section: Methodsmentioning
confidence: 99%
“…Vasopressin and electrolytes. Urine from NSE-AT1A transgenic (n ϭ 30) and control littermates (n ϭ 36) was analyzed for vasopressin levels using radioimmunoassay, as described (7). In addition, urines were diluted (1:4), and osmolality was determined using a vapor pressure osmometer (Wescor Instruments).…”
Section: Methodsmentioning
confidence: 99%
“…Centrally administered ACh or cholinergic agents increase arterial BP [53] because of the increase in sympathetic nerve tone and the acceleration of vasopressin release [53][54][55]. Systemic injection of ChE inhibitor increases systolic and diastolic BP [27,56].…”
Section: Effect Of Inhibition Of Cholinesterase On Arterial Blood Prementioning
confidence: 99%
“…Among factors affecting electrophysiological properties of vasopressinergic neurons and release of vasopressin are noradrenaline, gamma-aminobutyric acid (GABA) and glutamate. It has been shown that neurosecretory cells of SON and PVN nuclei receive inputs from A1 noradrenergic, GABAergic and glutamatergic neurons of the brain stem and forebrain [44][45][46][47][48][49][50][51]. Effectiveness of these neurotransmitters is modulated by several locally acting neuropeptides and by gasotransmitters, specifically by angiotensin II, cytokines, and nitric oxide, and by some other local factors [52][53][54][55][56][57].…”
Section: Central and Peripheral Vasopressin Systemsmentioning
confidence: 99%